THE FORMATION OF A POLITICAL IDENTITY - Tatiana Bagirovna Legenina (Современная наука и инновации, 2022)
His article deals with the problem awareness of the individual political identity. he author describes the types of political identity and considers the role of personal experience of the individual in the process of formation of political identity.